The Role of Social, Cultural, and Economic Environments in Determining Employment Opportunities for Vocational High School Graduates - Utomo, Joko Budi; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study explores the role of social, cultural, and economic environments in determining employment opportunities for vocational high school graduates, with a case study at SMKN 1 Mondokan, Indonesia. Using a qualitative case study approach, data were collected through indepth interviews, participant observation, and documentation involving students, alumni, teachers, parents, and industry partners. The results show that the social environment, particularly family support, teacher guidance, and peer influence plays a significant role in shaping graduates' readiness and access to employment. Culturally, local values, societal norms, and school work culture influence graduates' career perceptions and decisions, often creating tension between vocational ideals and traditional community expectations. Economically, the financial condition of graduates' families and the limited availability of local job opportunities significantly impact employment outcomes. Many graduates are compelled to work outside their area of expertise due to economic pressures or the lack of industry-aligned opportunities. Furthermore, although the school has implemented vocational programs such as internships, teaching factories, and entrepreneurship education, collaboration with industry remains inconsistent and fragmented. The study concludes that enhancing employment prospects for vocational graduates requires a systemic integration of educational institutions, industry partnerships, family involvement, and culturally adaptive career guidance. The findings contribute to strengthening the link between vocational education and the labor market, especially in semi-rural settings.